MENINGKATKAN PEMAHAMAN PESERTA DIDIK DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERBASIS MODEL PEMBELAJARAN INQUIRY KELAS VII DI SMPN 4 BAJAWA - Melkior Wewe; Sofia Ari (Jurnal Ilmiah Mandalika Education (MADU), 2024)
This study aims to improve students' understanding in solving mathematical story problems using the Inquiry-based learning model for Grade VII students at SMPN 4 Bajawa. The study employed an experimental design with purposive sampling technique. Data collection was conducted through document recording, observation, questionnaire, and test methods. The results showed that the Inquiry-based learning model can enhance students' learning activities and academic achievement. Students' learning activities increased with the use of the Inquiry-based learning model, and their academic achievement also improved. The conclusion of this study is that there is an increase in students' learning activities and academic achievement with the use of the Inquiry-based learning model.